Influence of growth kinetics on Sn incorporation in direct band gap Ge1−xSnx nanowires. Issue 32 (2nd August 2018) - Doherty, Jessica; Biswas, Subhajit; Saladukha, Dzianis; Ramasse, Quentin; Bhattacharya, Tara Shankar; Singha, Achintya; Ochalski, Tomasz J.; Holmes, Justin D.
Abstract : An investigation of the influence of growth kinetics on Sn incorporation in Ge1− x Sn x nanowires. Abstract : Ge1− x Sn x alloys with substantial incorporation of Sn show promise as direct bandgap group IV semiconductors. This article reports the influence of growth kinetics on Sn inclusion in Ge1− x Sn x alloy nanowires through manipulation of the growth constraints, i.e. temperature, precursor type and catalyst. Ge1− x Sn x nanowire growth kinetics were manipulated in a vapour–liquid–solid (VLS) growth process by varying the growth temperature between 425 and 470 °C, using Au and Ag alloys as growth catalysts and different tin precursors such as allyltributytin, tertaethyltin and tetraallyltin. The profound impact of growth kinetics on the incorporation of Sn; from 7 to 9 at%; in Ge1− x Sn x nanowires was clearly apparent, with the fastest growing nanowires (of comparable diameter) containing a higher amount of Sn. A kinetically dependent "solute trapping" process was assigned as the primary inclusion mechanism for Sn incorporation in the Ge1− x Sn x nanowires. The participation of a kinetic dependent, continuous Sn incorporation process in the single-step VLS nanowire growth resulted in improved ordering of the Ge1− x Sn x alloy lattice; as opposed to a randomly ordered alloy. The amount of Sn inclusion and the Sn impurity ordering in Ge1− x Sn x nanowires has a profound effect on the quality of the light emission and on the directness of the band gap as confirmed by temperature dependent photoluminescence study and electron energy loss spectroscopy.